2009
DOI: 10.1210/jc.2009-0483
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Recurrent Sleep Restriction in the Setting of High Caloric Intake and Physical Inactivity Results in Increased Insulin Resistance and Reduced Glucose Tolerance

Abstract: Experimental bedtime restriction, designed to approximate the short sleep times experienced by many individuals in Westernized societies, may facilitate the development of insulin resistance and reduced glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
257
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(280 citation statements)
references
References 33 publications
18
257
3
2
Order By: Relevance
“…Sleep restriction was associated with reduced insulin sensitivity in all the studies (except one (30) ), with reduced glucose tolerance in one of them (27) . The study that found no effect on glucose or insulin aimed to determine the hormonal effects of restricting sleep duration under controlled feeding conditions (30) .…”
Section: Evidence From Sleep Restriction Clinical Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Sleep restriction was associated with reduced insulin sensitivity in all the studies (except one (30) ), with reduced glucose tolerance in one of them (27) . The study that found no effect on glucose or insulin aimed to determine the hormonal effects of restricting sleep duration under controlled feeding conditions (30) .…”
Section: Evidence From Sleep Restriction Clinical Studiesmentioning
confidence: 87%
“…Multiple small laboratory-based crossover studies on healthy young participants have looked at the effect of sleep restriction on insulin sensitivity and glucose tolerance (26)(27)(28)(29)(30) . Sleep restriction was associated with reduced insulin sensitivity in all the studies (except one (30) ), with reduced glucose tolerance in one of them (27) .…”
Section: Evidence From Sleep Restriction Clinical Studiesmentioning
confidence: 99%
“…Additionally, night‐time NSHEs directly compromise patients’ quality of sleep. This is a concern, because disruption to sleep has been associated with metabolic abnormalities that can increase the risk of future hypoglycemic episodes, creating a vicious cycle12, 13.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased sleep in humans is associated with weight gain, higher body mass index (BMI), greater body-fat percentage (Cappuccio et al, 2008;Patel and Hu, 2008), and impaired glucose metabolism (Hanlon and Van Cauter, 2011;Nedeltcheva et al, 2009). Remarkably, recent studies have shown that the positive energy-balance state incurred by sleep loss is accounted for by increased caloric intake outside of regular meals ('snacking'; Markwald et al, 2013), particularly on carbohydrate-or fat-enriched foods (Markwald et al, 2013;Nedeltcheva et al, 2009;Spiegel et al, 2004a;St-Onge et al, 2011;Weiss et al, 2010). There is much interest in identifying the physiological basis of these behavioral changes, and studies to date have focused mainly on peripheral endocrine systems (eg, leptin and ghrelin) that regulate feeding in conjunction with energy-balance fluctuations.…”
Section: Introductionmentioning
confidence: 99%